An empirical study on the possibility of Financial Integration between the Stock Exchanges of North African Countries - frahi, fadila (Journal of Research in Finance and Accounting, 2022)
This study aims to investigate the possibility of achieving Financial Integration between the Stock Exchanges of North African Countries, and the impact of the performance of certain Economic and Financial variables on Economic growth in light of this integration. For this purpose, the Co-integration methodology (ARDL) and the Panel pooling model for quarterly data were used during the period 2010-2020. The study concluded that there is no Co-integration between the Four Countries, while there is the possibility of bilateral Co-integration between Algeria and Tunisia, As the study indicates in the recommendations, there is a need to merge mechanisms for cooperation between these Stock Exchanges, especially in light of the Stocks Markets being affected by regional blocs and rapid global transformations.